2013
DOI: 10.1128/aac.00794-13
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Level of Undecaprenyl Pyrophosphate Synthase Has Complex Effects on Susceptibility to Cell Wall Antibiotics

Abstract: Undecaprenyl pyrophosphate synthase (UppS) catalyzes the formation of the C 55 lipid carrier (UPP) that is essential for bacterial peptidoglycan biosynthesis. We selected here a vancomycin (VAN)-resistant derivative of Bacillus subtilis W168 that contains a single-point mutation in the ribosome-binding site of the uppS gene designated uppS1. Genetic reconstruction experiments demonstrate that the uppS1 allele is sufficient to confer low-level VAN resistance and causes reduced UppS translation. The decreased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…However, recent work has suggested that available undecaprenylphosphate might serve as the signal that is sensed by the anti-σ M factors YhdK/L to maintain inhibition of σ M (22,23). Our results are consistent with this idea.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, recent work has suggested that available undecaprenylphosphate might serve as the signal that is sensed by the anti-σ M factors YhdK/L to maintain inhibition of σ M (22,23). Our results are consistent with this idea.…”
Section: Discussionsupporting
confidence: 83%
“…amj is regulated by the stress-response sigma factor σ M . σ M is held inactive by the two integral membrane proteins YhdL and YhdK, and inhibition is relieved in response to an unknown signal that is thought to be generated by cell wall stress (21)(22)(23). Expression profiling experiments indicate that σ M -controlled genes are transcribed at low levels under normal growth conditions and are induced twoto fivefold in response to acute exposure to cell wall synthesis inhibitors (19,24).…”
Section: Significancementioning
confidence: 99%
“…Specifically, the M regulon is selectively induced by UPP-Pase depletion, with comparatively weak effects noted for other ECF factor stress responses. Induction of the M regulon is consistent with the inclusion of the BcrC UPP-Pase as part of this regulon (19), as well as the previously noted induction in cells treated with bacitracin (48) or containing mutations that decrease UPP synthesis (17). In contrast with M , the W regulon, most strongly activated by membrane stress conditions (50), was downregulated in the depleted cells compared to its expression in the control.…”
Section: Figmentioning
confidence: 55%
“…The depletion strain was not significantly more sensitive to several other tested stress conditions, including compounds that elicit membrane stress (nisin, SDS, and Triton X-100). The reason for the increased sensitivity to some but not other peptidoglycan synthesis inhibitors is presently unclear, but interpreting such effects can be complex, as discussed previously (17).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation